LEGAL NATURE INSTITUTE OF MORTGAGE - Майданик, Р. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article are examined the grounds of origin of mortgage and its maintenance as a «thing» right. Author grounds an idea that an agreement of mortgage of habitation is real agreement institution of providing type, the article of which makes the habitation which is acknowledged the real estateand object of right of ownership built and put into operation.